2005
DOI: 10.1111/j.1523-5378.2005.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like Receptor 2‐Mediated Gene Expression in Epithelial Cells During Helicobacter pylori Infection

Abstract: The current study investigated the TLR2-mediated global gene changes after H. pylori stimulation in the epithelial cell system. This approach will be helpful in identifying genes whose expression is mediated by specific TLRs and in determining the cellular responses that are responsible for diverse signal pathways during H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 52 publications
1
51
2
Order By: Relevance
“…Interestingly, Ikeda et al (2007) reported that pre-incubation of rat biliary epithelial cells with anti-TLR4 or anti-TLR2 antibodies downregulated MUC2 expression induced by LPS. In contrast, TLR2 and bacterial components induced expression of MUC2 in cultured gastric epithelial cell lines and were activated by nuclear factor (NF)-kB (Ding et al, 2005;Ikeda et al, 2007). All of these results, including ours, suggest that G. seoi antigen induces MUC2 expression via the activation of the TLR pathways in human IECs.…”
Section: Discussioncontrasting
confidence: 40%
“…Interestingly, Ikeda et al (2007) reported that pre-incubation of rat biliary epithelial cells with anti-TLR4 or anti-TLR2 antibodies downregulated MUC2 expression induced by LPS. In contrast, TLR2 and bacterial components induced expression of MUC2 in cultured gastric epithelial cell lines and were activated by nuclear factor (NF)-kB (Ding et al, 2005;Ikeda et al, 2007). All of these results, including ours, suggest that G. seoi antigen induces MUC2 expression via the activation of the TLR pathways in human IECs.…”
Section: Discussioncontrasting
confidence: 40%
“…Ding et al also reported that H. pylori activates MAP kinase pathways, and treatment with an ERK1/2 inhibitor resulted in accumulation of cells at the G 0 /G 1 stage (6). Earlier, Ding et al had used a microarray to screen genes induced by H. pylori and tested the dependence of the induction on TLR2, using HEK cells with or without the transfection of TLR2 expression plasmid (7). Genes upregulated in a TLR2-dependent way during H. pylori infection were IL-8, growth-related oncogenes, and molecules contributing to NF-B pathways.…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6] For example, CDX2 expression was reportedly upregulated in cultured epithelial cells when they were infected with bacteria, and interactions of TLR with microbial components are involved in the regulation of MUC expression. [30][31][32][33][34][35] Therefore, bacterial components in bile may induce CDX2 expression and then aberrant MUC2 expression in the ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preincubation with anti-TLR4 antibody or anti-TLR2 antibody downregulated CDX2 and MUC2 expression in BECs induced by LPS (a ligand for TLR4) or Pam3 (a ligand for TLR2), respectively, Interaction of TLR with PAMPs is known to activate intracellular signals followed by NF-kB translocation and the synthesis of molecules including inflammatory cytokines. 24,35 The involvement of TLR2 and/or TLR4 in Helicobacter pylori infections has been revealed in cultured gastric epithelial cell lines, 33,34 in which MUC2 was induced to express by TLR2/ bacterial components and the activation of NF-kB. 3,31,32 PAMPs-induced CDX2 and MUC2 overexpression via an NF-kB pathway located downstream of TLRs.…”
Section: Intestinal Metaplasia Of Bile Ducts H Ikeda Et Almentioning
confidence: 99%